Ecotoxicologically relevant cyclic peptides from cyanobacterial bloom (Planktothrix rubecens) - a threat to human and environmental health - Sedmak, Bojan (Radiology and oncology (Ljubljana), 2008)
Background. The information of the overall production of major cyanobacterial cyclic peptides in a water body is essential for risk assessment and for the prediction of future development of the bloom. A procedure that gives a reviewof both toxic and non-hepatotoxic hydrophilic cyclic peptide production is important to evaluate the ecological conditions in the water environment and to predict the release of dangerous toxic and tumour promoting substances.Methods. The cyclic peptides were identified on the basis of their retention times, characteristic spectra, molecular masses and biological activity. The non-hepatotoxic cyclic peptides were characterised by their inhibition of porcine pancreatic elastase, while cytotoxicity to mammalian cells was tested with the MTT test on B16 cell line. Conclusions. The method presented gives a rapid, simultaneous assessment, preliminary identification and estimation of bioactive cyclic peptides. The synthesis of non-hepatotoxic cyclic peptides can mediate the release various toxic and otherwise biologically active substances that induce systemic genotoxicity in mammals.
Keywords: cianobakterije; cistini; peptidi; planktopeptin; sesalci; škodljivost; toksičnost; tumorski promotorji; vodno okolje